Research into cancer metabolomics: Towards a clinical metamorphosis. (July 2015) - Olivares, Orianne; Däbritz, J. Henry M.; King, Ayala; Gottlieb, Eyal; Halsey, Christina
Highlights: Metabolism-related tools are employed to diagnose and treat cancer. Promising metabolic tracers and anti-cancer drugs are in clinical trials. Metabolomics provides new information on the vulnerabilities of malignant diseases. Abstract: The acknowledgement that metabolic reprogramming is a central feature of cancer has generated high expectations for major advances in both diagnosis and treatment of malignancies through addressing metabolism. These have so far only been partially fulfilled, with only a few clinical applications. However, numerous diagnostic and therapeutic compounds are currently being evaluated in either clinical trials or pre-clinical models and new discoveries of alterations in metabolic genes indicate future prognostic or other applicable relevance. Altogether, these metabolic approaches now stand alongside other available measures providing hopes for the prospects of metabolomics in the clinic. Here we present a comprehensive overview of both ongoing and emerging clinical, pre-clinical and technical strategies for exploiting unique tumour metabolic traits, highlighting the current promises and anticipations of research in the field.